An innovative approach to NC programming for accurate five-axis flank milling of spiral bevel or hypoid gears. (March 2017) - Zhou, Yuansheng; Chen, Zezhong C.; Tang, Jinyuan; Liu, Shengjun
Abstract: To transfer power, a pair of spiral bevel or hypoid gears engages. From beginning to end of two tooth surfaces engaging with each other: for their rigid property, they contact at different points; and for their plastic property, they contact at small ellipses around the points. On each surface, the contact line (or called as contact path) by connecting these points and the contact area by joining these ellipses are critical to driving performance. Therefore, to machine these surfaces, it is important to machine the contact line and area with higher accuracy than other areas. Five-axis flank milling is efficient and is widely used in industry. However, tool paths for flank milling the gears, which are generated with the existing methods, can cause overcuts on the contact area with large machining errors. To overcome this problem, an innovative approach to NC programming for accurate and efficient five-axis flank milling of spiral bevel or hypoid gears is proposed. First, the necessary conditions of the cutter envelope surface tangent with the designed surface along a designed line are derived to address the overcut problem of five-axis milling. Second, the tooth surface including the contact line and area are represented using their machining and meshing models. Third, according to the tooth surface model, an optimization method based on the necessary conditions is proposed to plan the cutter location and orientation for flank milling the tooth surface. By using these planned tool paths, the overcut problem is eliminated and the machining errors of contact area are reduced. The proposed approach can significantly promote flank milling in the gear manufacturing industry. Highlights: Five-axis flank milling is applied to manufacture spiral bevel or hypoid gears. Tangency is formulated for cutter envelope and designed surfaces along a given line. An closed-form approximate model is proposed to represent geometric deviations. Geometric deviations are minimized to contact area rather than whole tooth surface.